^{2}-1)=7x+13 solve an sum of two roots

2(x^{2}-1)=7x+13 solve an sum of two roots

Tutors, sign in to answer this question.

If a(x-b)(x-c)=0,

then ax^2 - a(b+c)x + bc = 0.

The sum of the two roots is the opposite of the coefficient of the linear term divided by the leading coefficient.

Tom's 3rd line is 2x^2 - 7x -15 = 0.

We can immediately say the sum of the roots is 7/2.

2(x^2 -1) = 7x + 13

2x^2 - 2 = 7x +13

2x^2 - 7x -15 = 0

Factoring we get

(2x + 3) (x - 5) = 0

2X + 3 =0

2X = -3

X = -3/2

AND

x - 5 =0

x = 5

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.